Chemistry Learning Anxiety Profile of Phase E Students of Public Senior High School in Sleman Regency - Hindun Hindun; Heru Pratomo (Universitas Negeri Yogyakarta, 2024)
Chemistry is still considered a subject that is difficult for some students to understand, thus triggering chemistry learning anxiety or chemophobia. This research aims to analyze the level of anxiety in studying chemistry in tenth-grade students at public senior high schools in Sleman Regency in participating in phase E chemistry learning. This quantitative research uses a survey method with a cross-sectional design. A total of 413 tenth-grade students from six public senior high schools in Sleman Regency were selected using cluster random sampling as the research sample. The instrument used is the chemistry learning anxiety scale, which consists of 50 statement items. The data results were analyzed using ideal assessment categories. The findings of this research revealed that students have low anxiety about studying chemistry in the phase E of chemistry learning. Low chemistry learning anxiety is a good asset for students to be able to follow and understand chemistry learning well in phase E and the following phases. Male students and students with good academic achievement tend to have lower chemistry learning anxiety than female students and students with less good academic achievement.